(untitled) (Biological Sciences - PJSIR, 2010)
Evaluation of the nutritional value and antioxidant activity of Punica granatum peel extracts for their radical scavenging activity revealed that potent antioxidant activity, in the order of ethyl acetate fraction > chloroform fraction > petroleum ether fraction > water fraction. Ethyl acetate fraction had higher radical scavenging activity in comparison to a standard antioxidant like BHT.